1999
DOI: 10.1093/molehr/5.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Expression of intercellular adhesion molecules ICAM-1 and ICAM-2 in human endometrium: regulation by interferon-gamma

Abstract: The purpose of this study was to localize intercellular adhesion molecule (ICAM)-1 and ICAM-2 in human endometrium and myometrium throughout the menstrual cycle, and to determine whether the expression of these molecules is regulated by interferon (IFN)-gamma. ICAM-1 and ICAM-2 distribution was examined in endometrial biopsies by immunocytochemistry, and Northern blotting was used to quantify ICAM-1 and ICAM-2 mRNA expression in isolated endometrial glands. Stromal fibroblast cultures were exposed to IFN-gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
3
33
0
1
Order By: Relevance
“…The fact that TNF produced a strong augmentation of ICAM1 protein in both endometrial cell homogenates is in accord with other studies (Rothlein et al 1988, Vigano et al 1994, Thomson et al 1999, Wu et al 2004) that demonstrate the strong ICAM1 induction mediated by proinflammatory cytokines in endometrial cultures, stimulation not observed on its mRNA suggesting posttranscriptional regulation of ICAM1 in long period of cell culture. Among the possible pathways by which TNF could mediate this increase is through the NFKB1 pathway, as it has been described in ectopic endometrial lesions in patients with endometriosis (Gonzalez-Ramos et al 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fact that TNF produced a strong augmentation of ICAM1 protein in both endometrial cell homogenates is in accord with other studies (Rothlein et al 1988, Vigano et al 1994, Thomson et al 1999, Wu et al 2004) that demonstrate the strong ICAM1 induction mediated by proinflammatory cytokines in endometrial cultures, stimulation not observed on its mRNA suggesting posttranscriptional regulation of ICAM1 in long period of cell culture. Among the possible pathways by which TNF could mediate this increase is through the NFKB1 pathway, as it has been described in ectopic endometrial lesions in patients with endometriosis (Gonzalez-Ramos et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Cell adhesion molecules (CAM), important mediators of these interactions, are functional receptors expressed on the cell membrane that participate actively in multiple physiological processes, such as leukocyte migration and activation, and also in pathological processes, such as tumor dissemination and metastasis (Dejana 2004, Gavert et al 2007, Fan et al 2009). Endometrial cells normally express adhesion molecules such as intercellular adhesion molecule-1 (ICAM1), a 90 kDa glycoprotein member of the immunoglobulin family, which is constitutively expressed by epithelial cells; however, it is expressed in a regulated pattern by stromal cells from endometrium during the menstrual cycle (Thomson et al 1999). ICAM1 function is related to the interaction between ICAM1 positive cells and cells from the immune system through the antigen lymphocyte function-associated antigen-1 (ITGAL) expressed on the leukocyte surface, modulating the cytotoxic activity of CD8C leucocytes and natural killer (NK) cells (Rothlein et al 1988, Tabibzadeh et al 1994, Vigano et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Tf culture: cell monolayers were cultured for 48 h in medium supplemented with the major iron transport protein, transferrin (Tf; 4 mg/ml; Sigma, St. Louis, Mo., USA), as a source of iron. (3) IFN-␥ culture: cell monolayers were cultured for 48 h in medium supplemented with interferon-␥ (IFN-␥ ; 100 ng/ml; Sigma), an inducer of ICAM-1 expression in endometrial cells [27,28] .…”
Section: Experimental Designmentioning
confidence: 99%
“…However, little information is available on the expression of ICAM-1 and VCAM-1, or its regulation in the endometrium. It has been localized in vivo in endometrial biopsies, mainly by immunohistochemical staining on paraffin sections or on cryosections of normal endometrium [9][10][11][12] and Northern blotting [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation